The Effects of a Walking Program on Older Chinese American Immigrants With Hypertension: A Pretest and Posttest Quasi-Experimental Design - Chiang, Chun-Ying; Sun, Fan-Ko (Public health Nursing, 2009)
ABSTRACT Objective: Hypertension is known to have high rates among Chinese Americans. Identifying culturally specific interventions to reduce sedentary behavior may be effective in reducing hypertension. This study examines the effects of an 8‐week walking program with and without cultural modification. Design: The study used a 2‐group, pretest and posttest, quasi‐experimental design. Sample: A total sample of 128 Chinese American immigrants with hypertension were assigned to walking groups. Results: The results showed that the walking program had no significant effects upon participant blood pressure or walking endurance. The results also revealed that individuals in the maintenance stage walked longer than those in the preparation stage. A comparison of demographic data showed that subjects with a lower level of education walked more minutes per week, which contributed to lower systolic blood pressures among this group as compared with those with a higher level of education. Conclusions: These results suggest that this walking protocol, when translated into Chinese and when accompanied by a weekly telephone reminder and other interactions with a Chinese‐speaking nurse, is appropriate to use without additional cultural modification. Future research should examine other components of Chinese culture or should apply this protocol for a longer period of time.